El Impacto de los Dispositivos Móviles en el Fomento de la Lectura Crítica en Jóvenes Pertenecientes a la Junta de Acción Comunal del Conjunto Residencial San Jerónimo de Yuste (2022)
Starting to read is of vital importance at the moment of wanting to have a position in front of some topics, since reading and reading critically makes the student or Whoever reads can acquire a look on a specific topic. also allows analyze from different angles the language and the way of perceiving and understanding the world. It influences how a social reality is identified in a contextualized way, being this is something essential to understand a text (Vivanco, 2018). Reading is an activity that starts from a very early age, this process opens the doors for education and writing that are important processes in the formation intellectual property of people (Valencia, 2004). There are different types of reading such as the literal, inferential and critical level, which tend to adapt to the needs of the reader, for example, a deep reading requires greater concentration and attention by part of the reader, while a speed reading seeks to detect important parts of a text and not deepen. There are these three levels in reading (literal, inferential and critical), but this work is focuses on addressing critical reading, on how to strengthen the processes to develop it in young people since reading critically and consciously helps the person to discover the historical, social, economic, and cultural context of the texts, places, and people about which which is read Critical reading allows access to critical thinking, which fulfills a fundamental role in the formation of self-aware and responsible citizens themselves and about others.